Respuesta :
If you would like to solve the system of equations, you can calculate this using the following steps:
6x – 3y = 3
–2x + 6y = 14 /*3
_________
6x – 3y = 3
–6x + 18y = 42
_________
-3y + 18y = 3 + 42
15y = 45
y = 45/15
y = 3
6x – 3y = 3
6x - 3 * 3 = 3
6x = 3 + 9
6x = 12
x = 12/6
x = 2
(x, y) = (2, 3)
The correct result would be (2, 3).
6x – 3y = 3
–2x + 6y = 14 /*3
_________
6x – 3y = 3
–6x + 18y = 42
_________
-3y + 18y = 3 + 42
15y = 45
y = 45/15
y = 3
6x – 3y = 3
6x - 3 * 3 = 3
6x = 3 + 9
6x = 12
x = 12/6
x = 2
(x, y) = (2, 3)
The correct result would be (2, 3).